Mechanisms and Cardiorenal Complications of Chronic Anemia in People with HIV - Kingsley Kamvuma; Benson M. Hamooya; Sody Munsaka; Sepiso K. Masenga; Annet Kirabo (Viruses, 2024)
Chronic anemia is more prevalent in people living with HIV (PLWH) compared to the general population. The mechanisms that drive chronic anemia in HIV are multifaceted and include functional impairment of hematopoietic stem cells, dysregulation of erythropoietin production, and persistent immune activation. Chronic inflammation from HIV infection adversely affects erythropoiesis, erythrocyte lifespan, and erythropoietin response, leading to a heightened risk of co-infections such as tuberculosis, persistent severe anemia, and increased mortality. Additionally, chronic anemia exacerbates the progression of HIV-associated nephrotoxicity and contributes to cardiovascular risk through immune activation and inflammation. This review highlights the cardinal role of chronic inflammation as a link connecting persistent anemia and cardiovascular complications in PLWH, emphasizing the need for a universal understanding of these interconnected pathways for targeted interventions.